1998
DOI: 10.1097/00004872-199816121-00036
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of urinary microalbumin excretion and ambulatory blood pressure in patients with essential hypertension

Abstract: In patients with essential hypertension, circadian changes in activity and variation of BP influence UAE/h, but no definite relationship of this kind was observed in patients with diabetes mellitus. Measurement of circadian changes in UAE or UAE/day may be useful in estimating the degree of daily stress in non-diabetic patients with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Whether a urine sample is centrifuged, filtered, or not treated, the albumin concentration decreases by 0.27%/day at Ϫ20°C but shows no decreases over 160 days at Ϫ80°C (359 ). The urinary albumin excretion rate does not show marked diurnal variation in diabetes but does so in essential hypertension (360 ). A (moderate).…”
Section: Gppmentioning
confidence: 94%
“…Whether a urine sample is centrifuged, filtered, or not treated, the albumin concentration decreases by 0.27%/day at Ϫ20°C but shows no decreases over 160 days at Ϫ80°C (359 ). The urinary albumin excretion rate does not show marked diurnal variation in diabetes but does so in essential hypertension (360 ). A (moderate).…”
Section: Gppmentioning
confidence: 94%
“…Whether a urine sample is centrifuged, filtered, or not treated, the albumin concentration decreases by 0.27%/day at −20°C but shows no decreases over 160 days at −80°C (359). The urinary albumin excretion rate does not show marked diurnal variation in diabetes but does so in essential hypertension (360). …”
Section: Glucosementioning
confidence: 99%
“…In patients with essential hypertension, in fact, it was reported that the AER has a significant correlation with the mean values of the 24-hour BP [24,25]. When the BP and urine data were divided into five time periods of the day, a significant positive correlation between BP and AER was found in 78% of the patients with essential hypertension [26]. However, these studies did not examine a relationship between day-night rhythms of BP and AER.…”
Section: Discussionmentioning
confidence: 98%